Trajetórias da formação docente : o caso da licenciatura curta em ciências das décadas de 1960 e 1970 - Tavares, Daniele Aparecida de Lima (2006)
This work aimed to investigate the Science Teacher Initial Education in the 1960-1970, specifically the short term courses known as Licenciatura Curta em Ciências. These courses were approved for the first time in 1964 and modified in 1971. We studied two historical moments 1960 and the 1970 based on new history methodologies. The research has used both written sources such as legal documents Indications, Resolutions, laws, papers article from the Cultura and Ciência Journal, papers from scientific congresses, books and etc and oral sources interviews with three teachers who participated actively in this historical process. The historical analysis allowed to understand how the economics, social and politics processes were transformed and influenced the preparation of science teachers. The work highlights the reasons why the proposals of the short term courses as solutions and justifications have been rejected by the educational communities.